تفعيل دور الرقابة الشرعية في الابتكار المصرفي الإسلامي - بوساحة, أ.محمد لخضر; بلحيمر, أ.د إبراهيم (Recherches économiques et managériales, 2016)
تهدف الدراسة إلى البحث في إمكانية تفعيل مساهمة هيئات الرقابة الشرعية في الابتكار بالمصارف الإسلامية،لأن المصداقية الشرعية ركن جوهري في منتجاتها المصرفية، وتعبير عن مصداقيتها أمام جمهور المتعاملين معها، بحكم أن واقع هيئات الرقابة الشرعية في المصارف الإسلامية يعبر عن عجزها في مسايرة بيئة معقدة و متغيرة تستلزم اندماج كل الأطراف في  في العملية الابتكارية بالمؤسسة ، ومما يؤكد حقيقتها أنها أصبحت عاجزة عن تقويم الأخطاء وتقديم البديل الشرعي،  حيث أصبحت أقرب إلى هيكل شكلي يضفي الصفة الشرعية على المنتجات المصرفية المقلدة، ومن هذا المنطلق إذا أريد لهيئات الرقابة الشرعية المساهمة في الابتكار المصرفي الأصيل دون تقليد،  يتحتم على إدارات المصارف الإسلامية إخراجها من دائرة المهام الشكلية  إلى دائرة الأعمال الطبيعية، من خلال الفصل بين مهام الفتوى ومهام التدقيق الشرعي، وربطهما بهيئات التطوير وفق آلية محكمة. الكلمات المفتاحية : المصارف الإسلامية ، الرقابة الشرعية ، الابتكار المصرفي . Summary  :    The study aims to explore the possibility of activating the contribution of legitimate oversight bodies in the innovation of Islamic banks, because the credibility of legitimate fundamental pillar of banking products, and an expression of its credibility in front of public clients, by virtue of the reality of the Shari'a in Islamic banking bodies expressed their inability to cope with the complex and the environment variable requires the integration of all parties in the process of innovative institution, and thus reality confirms that they become incapable of evaluating the errors and provide legitimate alternative, where he became closer to a formal structure legitimize counterfeit banking products such, it is this sense if the oversight bodies legitimacy to contribute to the banking innovation without authentic tradition, it is imperative on the Islamic banking departments out of the formal functions to the Department of natural Action Service, through the separation of the functions of the fatwa and the functions of the forensic audit, and linked bodies in accordance with the development of a mechanism court.and contributing to the banking innovation without authentic tradition. key words : Islamic banks,  Sharia Supervisory , banking innovation.